Spontaneous utero-cutaneous fistula between a benign uterine leiomyoma and abdominal skin: A case report - Kristi Bøgh Anderson; Erik Søgaard-Andersen; Ramune Aleksyniene; Anna Poulsgaard Frandsen (Elsevier, 2021)
The case of a 56-year-old woman with a fibroid uterus who developed utero-cutaneous fistula is presented. The woman was para 0, had an unremarkable medical history, and had no prior diagnosis of a gynecologic pathology, no operative interventions involving the uterine wall or any other risk factor for fistula. Abdominal examination revealed an abdominal mass with overlying deep, purulent ulceration. 18F-FDG PET/CT scan was consistent with uterine leiomyoma, but a differential diagnosis of sarcoma was considered due to the presence of the fistula, patchy increased FDG uptake of the tumor and several mildly enlarged lymph nodes bilaterally in the inguinal and iliac region. Hysterectomy with bilateral salpingo-oophorectomy was performed. Histological diagnosis was of leiomyoma with focal bizarre atypia, degenerative and metaplastic changes and utero-cutaneous fistula. To the best of our knowledge, this is the first case report describing a benign leiomyoma forming a fistula between the uterus and abdominal surface.